Parallel Phrases and Interaction in Greek and Latin Magical Texts.: The Pannonian Set of Curse Tablets - Barta, Andrea (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Magical texts represent an inexhaustible source for the phenomena of an ancient language for special purposes. The scope of this paper is limited to the different kinds of word-borrowings in the Pannonian set of curse tablets. One-language, well written and easily readable magical texts can be difficult to understand while explicit and unambiguous wording is expected in such practical genre like curses which level at definite persons. Harmful curse tablets and protective amulets, however, can be obscure. This study aims to give a comprehensive account of the possible reasons why these texts have a cloudy style, with special outlook of parallel phrases in Greek pieces of evidence.